Working for a Good Cause - Robert Dur; Robin Zoutenbier (Tinbergen Institute, 2011)
A rich literature in public administration has shown that public sector employees have stronger altruistic motivations than private sector employees. Recent economic theories stress the importance of mission preferences, and predict that altruistic people sort into the public sector when they subscribe to its mission. This paper uses data from a representative survey among more than 30.000 employees from 50 countries to test this prediction. Our results show that only those individuals who are willing to contribute to the welfare of others and, in addition, feel that by working in the public sector they contribute to a good cause are significantly more likely to work in the public sector. Our results are most pronounced for highly educated employees.
urn:NBN:nl:ui:15-1765/30601
Keywords: H1; J45; M5; 330; public service motivation; altruism; mission preferences; sorting; Öffentlicher Dienst; Leistungsmotivation; Altruismus; Soziale Werte; Schätzung; Welt